The Problem of Non-Muslims Witnessing the Hilal: Perspectives of Fiqh, Religious Court Judges, and Thomas Djamaluddin - Zulfian Wanandi; Nur Afdal Purnama Putra; Ulil Albab Al-Pateni; Yusuf Nur Qalbi; Kurniawan Kurniawan; Haikal Rivaldi (Astroislamica: Journal of Islamic Astronomy, 2025)
The position of non-Muslim testimony in the rukyat hilal has long been a discursion in astronomy, a very popular problem is what if the witness is indeed an expert in the field of astronomy and observation of celestial bodies. Therefore, this study aims to study the strength of the testimony of a non-Muslim witness in observing the hilal at the beginning of the hijri month by using the views of several figures, to achieve this goal the author in his research uses a qualitative research method with an analysis of several literature sources and also interview sources from related figures, the conclusion of this paper is the position of non-Muslim witnesses in the testimony of the hilal at the beginning of the month Hijri is acceptable but his position as a witness to the case and not a legal witness, another view says that his position is the same as the position of the camera in recording the image of the hilal.